Translation Challenges and Strategies: A Review of Theories - Pirman Ginting (LPPM STKIP AL MAKSUM, 2022)
In the process of translating, the translator strives to represent the meaning and style of the original text as correctly and precisely as possible. Since the translation accurately captures what the words imply, its meaning is the substance of the original text. Creating identical meanings between the source and target languages seems to be a challenge because of the clear differences in the cultures that the languages have. The disparate characteristics as the result of the distinct cultural elements require a translator to employ translation strategies based on the translation complexity levels. This implies that to produce a more contextually relevant and acceptable meaning, a translator may take a long time and require a lot of translation effort such as seeking the right type of translation strategy. The current paper aims at scrutinizing the translation problems and strategies from different theories. The theories are reviewed to unpack the translation problems that might happen and investigate the strategies from several hypotheses applicable to tackle the issues.